The Adjustment Mechanism to Differential Rates of Monetary Expansion among the Countries of the European Economic Community - Triffin, Robert; Grubel, Herbert (The Review of Economics and Statistics, 1962)
Robert Triffin, Herbert Grubel, The Adjustment Mechanism to Differential Rates of Monetary Expansion among the Countries of the European Economic Community, The Review of Economics and Statistics, Vol. 44, No. 4 (Nov., 1962), pp. 486-491